Peningkatan Aksesibilitas Wilayah Pesisir Kampung Della melalui Penanaman Pohon untuk Meningkatkan Ketahanan Lingkungan dan Akses Transportasi Berkelanjutan - Ihsan Febriadi; Achmad Rusdi; Renny Purnawati; Reyna Dwi Indira; Ramadhanti Marsaoly; Iman Islami; Indri Amilia Tupamahu; La Ibal (AJAD : Jurnal Pengabdian kepada Masyarakat, 2026)
Della Village, located in Selemkai District, Tambrauw Regency, Southwest Papua, is a remote coastal settlement with only one access road approximately one kilometer long and nearly 45 degrees steep. During the rainy season, this route often becomes impassable due to landslides and erosion, while the shoreline is vulnerable to abrasion caused by strong sea winds. This community service activity aims to improve accessibility through a vegetative approach, specifically planting trees to stabilize the slopes and protect the coast, thereby making transportation more sustainable. The participatory method includes socialization, collective planting, and maintenance planning. On August 18, 2025, 20 coastal tree seedlings (coconut and sea almond) were planted, with an additional plan to plant 51 more. Results showed significant improvement in community knowledge and understanding of the role of vegetation in erosion and abrasion mitigation.